2022
DOI: 10.1101/2022.03.26.485947
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structure of the connexin-43 gap junction channel in a putative closed state

Abstract: Gap junction channels (GJCs) mediate intercellular communication by connecting two neighboring cells and enabling direct exchange of ions and small molecules. Cell coupling via connexin-43 (Cx43) GJCs is important in a wide range of cellular processes in health and disease, yet the structural basis of Cx43 function and regulation has not been determined until now. Here we describe the structure of a human Cx43 GJC solved by cryo-EM and single particle analysis at 2.26 Å resolution. The pore region of Cx43 GJC … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 43 publications
3
19
0
Order By: Relevance
“…Because astrocytes may be responsible for the progression of ALS, drugs that block Cx43 hemichannels might be therapeutic [5]. One analysis of the Cx43 structure revealed a closed sieve-like molecular gate [16]. The Cx43 N-terminal domain is involved in channel gating and oligomerization and may control the switch between the channel’s open and closed states.…”
Section: Discussionmentioning
confidence: 99%
“…Because astrocytes may be responsible for the progression of ALS, drugs that block Cx43 hemichannels might be therapeutic [5]. One analysis of the Cx43 structure revealed a closed sieve-like molecular gate [16]. The Cx43 N-terminal domain is involved in channel gating and oligomerization and may control the switch between the channel’s open and closed states.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, several pore structures of connexins have recently been solved by Cryo-EM, opening the door for structureguided design of an activatable pore. [44][45][46][47][48] Here we report the light-activated assembly of a connexon nanopore in synthetic cells and the subsequent release of internal contents. We re-engineer connexin-43 (Cx43) 46,47 with a bulky protease recognition domain, which allows membrane-protein association but prevents nanopore function in the membrane.…”
Section: Introductionmentioning
confidence: 92%
“…Here we report the light-activated assembly of a connexon nanopore in synthetic cells and the subsequent release of internal contents. We re-engineer connexin-43 (Cx43) 46,47 with a bulky protease recognition domain, which allows membrane-protein association but prevents nanopore function in the membrane. After enzymatic digestion, Cx43 rapidly assembles into a functional nanopore, releasing contents into the extracellular space.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, comparative analysis between Cx26 [ 33 ] and Cx46/50 gap junctions [ 34 ], as well as the structure of Cx31.3 hemichannels [ 35 ] showed that the N-terminal domain appears to be involved in the gating mechanisms of gap junctions and hemichannels, adopting several conformations in different Cxs [ 36 ]. Disease-related mutations seem to be located in the extracellular loops, the pore region and the gating region.…”
Section: Structure Of Cxs and Panxsmentioning
confidence: 99%
“…At a pH of 6.9, the open state is favored: the transition between the closed and open state involves structural changes (in the secondary structure) in the first transmembrane domain, movement of the second to the fourth transmembrane domain and structural stabilization of the cytoplasmic loop [ 36 , 38 ]. The pharmacological inhibition of hemichannels formed by Cx43 have been tested in cerebral ischemia and in myocardial ischemia models, in which a large number of hemichannels are usually opened.…”
Section: Structure Of Cxs and Panxsmentioning
confidence: 99%